Assessing the Predictive Nature of Teacher and Student Writing Self-Regulation Discrepancy - Broda, Michael; Ekholm, Eric; Zumbrunn, Sharon (Frontline Learning Research, 2020)
In this study, we examine the extent to which the discrepancy between teacher-reported and student-reported self-regulatory behaviours during writing were associated with students’ end-of-year writing grades after controlling for student writing ability and other demographic characteristics. Results of our study, conducted with a sample of 201 middle grades students enrolled in a large, comprehensive suburban school district in the Mid-Atlantic U.S., suggest a significant and positive relationship between teacher discrepancy and grades, after controlling for writing ability, student self-regulation, gender, race/ethnicity, and SES. This has clear implications for the classroom, as it suggests that even after accounting for student difference in terms of ability background, and demographics, the effort that teachers perceive their students making in the fall are still associated with students’ year-end performance in their class. This represents some of the first frontline evidence of the predictive relationship between self-regulation discrepancy and student achievement in writing.